1990
DOI: 10.1210/jcem-70-1-234
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Corticoids: A New and Peculiar Stimulus of Growth Hormone Secretion in Man*

Abstract: It is widely accepted that chronic administration of corticoids in man inhibits the GH response to all of the stimuli tested so far. To study the action of corticoids administered acutely, several dexamethasone challenge tests were performed, after which GH levels were measured for 7 h. In eight volunteers, administration of 4 mg dexamethasone (Dex), iv, induced a clear-cut GH release compared with saline administration. The secretion followed an unusual pattern; basal GH levels (1.5 +/- 0.1 micrograms/L) star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
4

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 19 publications
6
69
2
4
Order By: Relevance
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 87%
“…This is due largely to actions of the steroids at the hypothalamic level which increase the expression and release of somatostatin (Papachristou et al, 1994;Fife et al, 1996;Lam & Srivastava, 1997) and decrease the production of GH releasing hormone (GHRH, Fernandez-Vazquez et al, 1995;Fife et al, 1996;Lam & Srivastava, 1997). Paradoxically, the impact of the consequent change in the hypothalamic drive to the somatotrophs is attenuated by concomitant actions of the steroids at the pituitary level which increase GHRH receptor (Tamaki et al, 1996;Miller & Mayo, 1997) and GH (Oosterom et al, 1983;Evans et al, 1992;Nogami et al,complicated by ®ndings in man that acute administration of GCs causes a transient (3 ± 4 h), but marked, increase in serum GH (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998). The mechanism by which the GCs evoke this secretory response is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute elevations of GH concentration in plasma may occur at the onset of the stress response, however, or after acute administration of glucocorticoids, presumably through stimulation of the GH gene by glucocorticoids through glucocorticoid-responsive elements in its promoter region. [82] In addition to the direct effects of glucocorticoids, which are pivotal in the suppression of growth observed in prolonged stress, increases in somatostatin secretion caused by CRH, with resultant inhibition of GH secretion, have been implicated as a potential mechanism of stress-related suppression of GH secretion. [83] In several stress system-related mood disorders with a hyperactive HPA axis, such as anxiety or melancholic depression, levels of GH or insulin-like growth factor-1 (IGF-1), or both, are significantly decreased.…”
Section: Growth Axismentioning
confidence: 99%
“…First, long-term exposure to glucocorticoids, as investigated in our study, may have different effects on Na + , K + -ATPase content than relatively short-term exposure. Similarly, GH secretion is acutely stimulated by administration of glucocorticoids such as dexamethasone [27,28]. However, long-term cortisol treatment suppresses GH secretion through increased somatostatin tone [29].…”
Section: Hormonal Regulation Of Na + K + -Atpase Contentmentioning
confidence: 99%